2008
DOI: 10.1021/jp804763y
|View full text |Cite
|
Sign up to set email alerts
|

Electron Confinement Effects in the EPR Spectra of Colloidal n-Type ZnO Quantum Dots

Abstract: Additional unpaired electrons have been introduced into colloidal ZnO quantum dots (QDs) photochemically and investigated by experimental and theoretical methods to test various possible descriptions of their wave functions. For n-type ZnO QDs with diameters between 3.0 and 7.0 nm, electron paramagnetic resonance (EPR) spectroscopy reveals size-dependent g* values in the range 1.960 < g* < 1.968 that are temperature independent and that rule out highly localized wave function descriptions. The size dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 44 publications
8
98
1
Order By: Relevance
“…Intrinsic defects in dilute magnetic semiconductors determine their electrical and magnetic properties. Investigation of donor and acceptor centers in ZnO nanocrystals by EPR is, therefore, quite important, and many EPR studies have been reported [19,[22][23][24][25][26][27], described briefly as follows. It was found that Li and Na, which are components of commonly used compounds for ZnO nanoparticle synthesis, act as shallow donors, and are located in the core of ZnO nanoparticle [22].…”
Section: Zno Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic defects in dilute magnetic semiconductors determine their electrical and magnetic properties. Investigation of donor and acceptor centers in ZnO nanocrystals by EPR is, therefore, quite important, and many EPR studies have been reported [19,[22][23][24][25][26][27], described briefly as follows. It was found that Li and Na, which are components of commonly used compounds for ZnO nanoparticle synthesis, act as shallow donors, and are located in the core of ZnO nanoparticle [22].…”
Section: Zno Quantum Dotsmentioning
confidence: 99%
“…On the other hand, H has also been found to act as a shallow donor, being located in Zn(OH) 2 capping shell covering the nanocrystal. In addition, Al, Ga, I also act as donors, whereas N acts as a shallow acceptor [19,24]. The effect of electron confinement was investigated in n-type ZnO quantum dots, in which the g value changes from 1.960 to 1.968 for nanoparticles with the sizes 3-7 nm [24].…”
Section: Zno Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also significant academic research interest in nano-systems as their properties are remarkably different from their bulk materials due to quantum confinement effect [1,2]. In quantum confinement theory, 1-dimensional confinement such as rods and wires increase carrier transport in light harvesting cells [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…46 By combining NIR and EPR measurements they unequivocally ascribed the signal at g ∼ 1.96 to free conduction band electrons.…”
Section: Tempol ↔ Tempol-h Interconversionmentioning
confidence: 99%